MENGUNGKAP KARAKTER MASYARAKAT MADURA MELALUI EKSPRESI KEBAHASAAN: KAJIAN LINGUISTIK ANTROPOLOGI - Muhammad Masqotul Imam Romadlani; Fitriyatuz Zakiyah (Universitas Galuh, 2023)
This research aims to examine the characteristics of the Madurese society through linguistic expressions regarding the emergence of the Covid19 pandemic. This research employs linguistic expressions posted in several Madurese instagram accounts such as @madura.receh, @maduraholic, @maduraenjoy, and @madura_konyol as data sources. Applying an anthropological linguistic approach, this research look carefully at the qualitative data to portray the cultural facts of the Madurese society in anthropological context through linguistic expressions at the beginning of Covid19 pandemic. Based on the findings, the linguistic expressions produced during the beginning of the pandemic demonstrate that the characters of the Madurese society can be drawn as a society that have very strong oral tradition, vicious religiosity, and they were characterized as a settled foreigner as well. The oral tradition can be found in the chanted poems commonly known as the paparèghân. Furthermore, lexical choice highly related to religious values such as sekobesah, pengeran, Sang Esa, faith, tawakkal, and tauhid illustrates their obedience and viscosity as a Moeslem. The character as a settled foreigner is indicated by linguistic expressions produced such as suggestions and short conversations between families in Madura and the settled foreigners to postpone their return due to the coronavirus pandemic.